Integrating generative artificial intelligence into Bakaran Batik: effects on design and workflow efficiency - Ardhianto, Peter; Susanto , Felicia Regina; Mulyanto, Vinke Almeyda (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
Artificial intelligence (AI) has been used in the development of design motifs for Bakaran Batik. This study investigates the methodological gaps in the production process, especially in the early stages of motif design, where traditional methods require a long time to design motifs, making them ineffective for clients with high demand and limited time. Qualitative methodology was used to collect data from two cross-generation batik companies. The data collection process included interviews, observations conducted before and after the application of AI, and literature analysis. Since 2023, AI technology for motif design has been applied in the Bakaran batik industry. AI generative motif design simplifies the batik pattern design process, allowing for a more measurable production process in terms of batik production time. The findings show a significant reduction in the time required for design and an increase in motif diversity. Batik artisans in Bakaran responded positively to the use of AI because it showed an increase in motif diversity and did not replace labor-intensive labor. However, the use of AI machines in motif design is less appropriate for certain clients who prioritize the motif design process through local wisdom such as fasting rituals, meditation or special inspiration from their batik makers. The use of AI has an impact on the Bakaran Batik industry including the potential for the growth of an innovative and sustainable economic system for its craftsmen considering the rarity of the younger generation who are engaged in the batik industry in Bakaran. The integration of AI in the motif creation process allows the batik business to preserve heritage motifs while increasing work productivity and overcoming creative challenges during motif design. This initiative ensures the long-term survival and expansion of Bakaran batik in the digital era.